Management of Recurrent or Progressing Skull Base Chondrosarcomas: Predictors of Long-Term Outcomes - Breshears, Jonathan D.; DeMonte, Franco; Habib, Ahmed; Gidley, Paul W.; Raza, Shaan M. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Skull base chondrosarcomas (CSA) are difficult tumors to cure and there is little data regarding salvage therapy.Objective This study aims to identify presentation and treatment-related factors which impact the progression free survival (PFS) and disease specific survival (DSS) for recurrent CSA, and to identify salvage treatment factors associated with successful restoration to the natural history following primary treatment.Methods This single-institution retrospective review included patients with recurrent/progressive CSA over a 25-year period. Survival analysis for factors impacting PFS and DSS was performed. Salvage treatment factors associated with achieving PFS ≥newly diagnosed median PFS were identified using univariate statistics. Analysis was performed on first recurrences and all recurrences combined.Results A total of 47 recurrence/progression events were analyzed from 17 patients (median two events/patient, range = 1–8). The overall PFS and DSS for the initial recurrence was 32 (range = 3–267) and 79 (range = 3–285) months, respectively. Conventional grade III or mesenchymal histology significantly predicted shorter PFS and DSS (p < 0.0001). After stratification by histology, previous radiation predicted shorter PFS for low-grade tumors (p = 0.009). Gross total resection (GTR) after a first time recurrence was significantly associated with successful salvage treatment (p < 0.05); however, this was rare.Conclusion In this series, high grade histology and prior radiation treatment negatively impacted salvage treatment outcomes, while GTR was associated with restoration to natural history following primary treatment. Careful consideration of histology, systemic disease status, previous treatments, and the anatomic extent of the skull base disease can optimize the outcomes of salvage intervention.
Keywords: skull base chondrosarcoma; recurrence; progression; salvage surgery